Transference Leadership For Heads Educational Management In AFIF Province And Its Relation With Job Satisfaction For Educational Supervisors - Al - Otaibi, Shadia Bint Najib (Journal of Educational and Psychological Sciences, 2019)
The study aimed to: - Identifying with the degree of The practice of heads educational management for type of transference leadership from the views of supervisors.- Acquaintance with the level of job satisfaction of educational supervisors in Afif Educational management.- Recognizing the statistical significance relation between the practice of heads educational management degrees' in Afif Educational management for the style of transference leadership and job satisfaction of educationalStudy Methodology: The researcher used the descriptive method (survey ) & descriptive method (Correlative)Study Population and Sample: The study population consists of all heads educational department and educational supervisor whether they are mails or females in Educational Management of AFIF.Study Tool: The researcher built tow questionnaires, the first questionnaire to measure using of the transference leadership and it consist of two parts one is personal information anther is phrases for measuring the practice of heads educational management degrees' in Afif Educational management from the points of view of educational supervisors , also it contain forth transference leadership diminutions( typical effective, mental- excitation, personal considerations, accusatory motivation) in (39) sentences.The second questionnaire to measure the level of educational supervisors' job satisfaction in (28) sentences. Moreover, the researcher used the fifth Grading scale to measure the responses of study sample.Study Results: the results of the study can firmed the following:- The overall average of total to the degree of transference leadership applying for Heads Department (4,10) , so this is the mean between fourth category which indicated to high degree.- The general average of the responses of the study sample at the axis of educational supervisors job satisfaction for in Educational management in AFIF that is mean (3,85 over 5) indicated to (high) degree of study tool.The results proved that there is connective, direct, strong relation & statistical function at (0,01) between the practice of heads educational management degrees' in Afif Educational management for the style of transference leadership and job satisfaction of educational. Also, the result show that connective the relation between general degree of the measure of transference leadership and general degree of the measure of job satisfaction is (0,56) , so it is positive direct relation.Study Recommendations:- Encouraging and training the Heads of educational management to be attention in knowing the weakness points about their work which is hinder the transference leadership practice.- Caring of training and qualifying staff who have primitive readiness for having transference leadership properties and characters.- Necessity of hold periodical specialist courses to create leaders and trine them about modern administrative styles that make job satisfaction for personnel.
Keywords: transformational leadership; Heads of education departments; Afif Governorate; Job Satisfaction; educational supervisors